Assessing the Thermal Performance of Phase Change Material in a Photovoltaic/Thermal System. (June 2016) - Browne, Maria C.; Quigley, Declan; Hard, Hanna R.; Gilligan, Sarah; Ribeiro, Nadja C.C.; Almeida, Nicholas; McCormack, Sarah J.
Abstract: Photovoltaic/ thermal (PV/T) systems refer to systems which integrate photovoltaic and solar thermal technologies and have the added advantage of producing both electrical and thermal energy. This study has been carried out to experimentally investigate the application of phase change material (PCM) in a thermal system under the climatic conditions of Ireland. In this system, a stainless steel container of PCM was integrated with a PV panel. PCM absorbs heat generated by the PV during daylight hours. Water is piped through the PCM and absorbs heat stored by the PCM. The application of the PCM alone was found to regulate the temperature of the PV panel by approximately 5 °C under climatic conditions of Ireland. This paper presents a method to assess the performance of a photovoltaic/thermal system with integrated PCM taking into account the useful heat energy gained by the water, stored by the PCM and the delay in available heat factor.